Evaluation of Humoral and Cellular Immune Responses to the SARS-CoV-2 Vaccine in Patients With Common Variable Immunodeficiency Phenotype and Patient Receiving B-Cell Depletion Therapy - Antolí, Arnau; Rocamora-Blanch, Gemma; Framil, Mario; Mas-Bosch, Virgínia; Navarro, Sergio; Bermudez, Carla; Martinez-Yelamos, Sergio; Dopico, Eva; Calatayud, Laura; Garcia-Muñoz, Nadia; Hernández-Benítez, Luis Humberto; Riera-Mestre, Antoni; et al. (Frontiers in Immunology, 2022)
Introduction: SARS-CoV-2 vaccines' effectiveness is not yet clearly known in immunocompromised patients. This study aims to assess the humoral and cellular specific immune response to SARS-CoV-2 vaccines and the predictors of poor response in patients with common variable immunodeficiency (CVID) phenotype and in patients treated with B-cell depletion therapies (BCDT), as well as the safety of these vaccines. Methods: From March to September 2021, we performed a prospective study of all adult patients who would receive the SARS-CoV-2 vaccination and were previously diagnosed with (i) a CVID syndrome (CVID phenotype group; n=28) or (ii) multiple sclerosis (MS) treated with B-cell depleting therapies three to six months before vaccination (BCD group; n=24). Participants with prior SARS-CoV-2 infection; or prior SARS-CoV-2 vaccine administration; or use of any immunosuppressant (except BCDT in MS group) were excluded. A group of subjects without any medical condition that confers immunosuppression and who met all study criteria was also assessed (control group; n=14). A chemiluminescence immunoassay was used to determine pre- and post-SARS-CoV-2 vaccine anti-S IgG antibodies. T-cell specific response was assessed by analysis of pre- and post-SARS-CoV-2 vaccination blood samples with an interferon-gamma release assay. The baseline blood sample also included several biochemical, haematological and immunological analyses. Results: SARS-CoV-2 vaccines are safe in immunocompromised patients, although their effectiveness was lower than in healthy individuals. CVID phenotype patients showed impaired humoral (29%) and cellular (29%) response, while BCD patients fundamentally presented humoral failure (54%). Low IgA values, low CD19+ peripheral B cells, low switched memory B cells, and a low CD4+/CD8+ ratio were predictors of inadequate specific antibody response in CVID phenotype patients. No factor was found to predict poor cellular response in CVID phenotype patients, nor a defective humoral or cellular response in BCD patients. Conclusion: The effectiveness of SARS-CoV-2 vaccines in CVID phenotype and BCD patients is lower than in healthy individuals. Knowledge of predictive factors of humoral and cellular response failure in immunocompromised patients could be very useful in clinical practice, and thus, studies in this regard are clearly needed.